The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.9744/ced.14.2.92-99
|View full text |Cite
|
Sign up to set email alerts
|

Increase on Strengths of Hot Weather Concrete by Self-Curing of Wet Porous Aggregate

Abstract: The compressive and tensile strengths of concrete made in hot weather condition decreased due to loss of mixing water caused by high evaporation. One method to overcome the problem is the use of saturated fly ash aggregate. The water content in fly ash aggregate can flow out to the hardened cement paste to continue the hydration process. This "self-curing" mechanism could produce more hydration around the surface of fly ash aggregate which subsequently increases concrete strength. Experimental study has been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…At 180 days, the rate of increase is 32% for limestone concrete, 25% for siliceous concrete, and 23% for silico-calcareous concrete. This significant improvement in strength was confirmed by researchers [34,35] who conducted a comparative study between water curing and curing with the use of curing agents. Their findings demonstrated that concrete treated with curing admixtures outperforms that cured solely in water.…”
Section: Figure 8 Effect Of Curing Compound On Concrete Compressive S...mentioning
confidence: 59%
“…At 180 days, the rate of increase is 32% for limestone concrete, 25% for siliceous concrete, and 23% for silico-calcareous concrete. This significant improvement in strength was confirmed by researchers [34,35] who conducted a comparative study between water curing and curing with the use of curing agents. Their findings demonstrated that concrete treated with curing admixtures outperforms that cured solely in water.…”
Section: Figure 8 Effect Of Curing Compound On Concrete Compressive S...mentioning
confidence: 59%
“…The additional mineral is reactive and contributes to the hydration process. The use of saturated fly ash is one way to reduce high exposure in the process of hydration to the density of cement in concrete [12,13]. The use of alternative sources for the manufacture of cement developed in Japan produced ecocement made from municipal waste ash through incineration as a substitute for some of the main raw materials containing 50% of cement raw materials such as mud waste [14].…”
Section: Imentioning
confidence: 99%
“…The curing agent moisture remains dormant until a humidity gradient forms during hydration, triggering a chemical reaction.[56]. Water is moving to dry zones of the matrix by capillary suction for continuous hydration[57]. PEG 400 is a revolutionary admixture that can transform concrete into a self-curing base.…”
mentioning
confidence: 99%